Absolute beginner's guide to winning presentations - Weissman, Jerry (Que, 2004)
Jerry Weissman, world-renowned guru of the corporate presentation and best-selling author, offers everyone, even absolute beginners, the benefit of his experience and expertise in crafting and delivering unforgettable speeches. Using the author's practical advice and step-by-step methods from his best-selling book, Presenting to Win, anyone can master the difficult task of communicating a call-to-action to others, be it a new customer, an employer, or an audience of hundreds. The key to Weissman's philosophy is discovering what in the presentation represents the "Aha!" moment for the audience. Instead of focusing on flashy PowerPoint gimmicks or crafting facts to prove a point, this book walks the reader through the entire preparation process from brainstorming ideas and creating a story to preparing the slides and delivering the speech. Using case studies from his work with companies like Yahoo!, Intel, Intuit, Cisco Systems, and Microsoft, Weissman demonstrates the techniques that have won him the respect and confidence of high-powered CEOs from around the world. After using this book to craft a high-quality message, even the most timid beginner will perform like a top-dollar, persuasive presenter with the audience feedback to prove it.